1990
DOI: 10.1111/j.1570-7458.1990.tb01379.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf age preference for opposition by three species of whitefly on lemon

Abstract: The leaf age preferences for oviposition by three species of whitefly (Dialeurodes citri [Ashmead], Aleurothrixusfloccosus [Maskell], and Parabemisia myricae [Kuwana]) were tested on lemon, Citrus limon (L.). Four categories of leaf age were tested (I: incompletely expanded, growing leaves; II: young leaves that are completely expanded but not yet dark green; III: completely mature leaves [dark green]; IV: completely mature leaves judged to be older than III as determined by the age of the twigs to which they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
1
10
0
1
Order By: Relevance
“…Oviposition preference for leaves of different age has been described for three whitefly (Homoptera: Aleyrodidae) species in both laboratory and field tests (Walker & Zareh, 1990). The authors found that Parabemisia myricae (Kuwana) preferred very young lemon leaves for oviposition.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Oviposition preference for leaves of different age has been described for three whitefly (Homoptera: Aleyrodidae) species in both laboratory and field tests (Walker & Zareh, 1990). The authors found that Parabemisia myricae (Kuwana) preferred very young lemon leaves for oviposition.…”
Section: Discussionmentioning
confidence: 87%
“…The authors found that Parabemisia myricae (Kuwana) preferred very young lemon leaves for oviposition. Previously it had been shown that this species only colonizes young leaves because the mature lemon leaf cuticle prevents colonization of mature leaves (for references see Walker & Zareh, 1990). Two other whitefly species, Aleurothrixus floccosus (Maskell) and Dialeurodes citri (Ashmead), however, do colonize older leaves.…”
Section: Discussionmentioning
confidence: 99%
“…The preference of whitefly adults to oviposit on the newly unfolded leaves (Noldus et al, 1985;Walker & Zareh, 1990;Sütterlin et al, 1991), results in high larval (L3, L4) densities on medium aged, fully expanded leaves. The preference of whitefly adults to oviposit on the newly unfolded leaves (Noldus et al, 1985;Walker & Zareh, 1990;Sütterlin et al, 1991), results in high larval (L3, L4) densities on medium aged, fully expanded leaves.…”
Section: Discussionmentioning
confidence: 99%
“…However, the actual number of generations that will develop in a year will be limited by the availability of young flush foliage throughout the year. The affinity of P. myricae for young foliage is not just a preference but is an absolute requirement for survival (WALKER and AITKEN 1985;WALKER and ZAREH 1990).…”
Section: Coefficients Of Variation and Deviations Between Predicted Amentioning
confidence: 99%